Discontinuity in Regulations Regarding Health Workers in Health Law Legislation with the Principle of Legal Certainty - Gultom Rosmaida Feriana; Zainal Arifin Hosein (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The discontinuity of regulations concerning health workers in health law legislation poses a challenge for the application of the principle of legal certainty in Indonesia. The principle of legal certainty is an essential foundation in the legal system that guarantees the rights and obligations of health workers and the community. However, there is a gap between the regulations for health workers and the principle of legal certainty, which impacts the clarity of the legal status, rights, and obligations of health workers. This research aims to examine the discontinuity between health workers' laws and the application of the principle of legal certainty, as well as the impact arising from this inconsistency. Additionally, this research identifies efforts that can be made to align labor regulation and health worker regulations with the principle of legal certainty. Using normative legal research methods through legislative and conceptual approaches, this study finds that regulatory harmonization is necessary to strengthen legal certainty in health worker regulation in Indonesia.